2013
DOI: 10.1016/j.optcom.2013.07.080
|View full text |Cite
|
Sign up to set email alerts
|

Measurements on release–recapture of cold 85Rb atoms using an optical nanofibre in a magneto-optical trap

Abstract: We have performed release-recapture temperature measurements of lasercooled 85 Rb atoms using an optical nanofibre (ONF) in a magneto-optical trap (MOT). The effects of changing the cooling laser light-shift parameter on the temperature of the cold atoms and spring constant of the trap are studied. By varying the cold atom number density near the ONF, the onset of the multiple scattering regime is observed without the need for an estimation of the atom cloud size. Moreover, this sensitive ONF assisted release-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Rb atoms were cooled and trapped using a standard magneto-optical trapping technique (for details see [15] though it was for 85 Rb). Base pressure in the vacuum chamber was 2 × 10 −9 mbar and, when a current of 5 A was passed through a Rb dispenser, the pressure rose to 4 × 10 −9 mbar and remained stable during the experiments.…”
Section: Magneto-optical Trapping Of Atoms 87mentioning
confidence: 99%
See 1 more Smart Citation
“…Rb atoms were cooled and trapped using a standard magneto-optical trapping technique (for details see [15] though it was for 85 Rb). Base pressure in the vacuum chamber was 2 × 10 −9 mbar and, when a current of 5 A was passed through a Rb dispenser, the pressure rose to 4 × 10 −9 mbar and remained stable during the experiments.…”
Section: Magneto-optical Trapping Of Atoms 87mentioning
confidence: 99%
“…Earlier experiments, such as those reported in [1][2][3][4][5], focussed on (i) the interaction of the light guided in the fundamental fibre mode, HE 11 , with atoms, or (ii) excitation of the HE 11 mode through fluorescence coupling from resonantly excited atoms. While the latter experimental technique provides a means of characterizing the atoms near the surface of the ONF [1,[13][14][15], the former permits scenarios whereby atoms can be trapped around the ONF when far-detuned light is coupled into it [2,3,5]. Such ONFs can be termed as single-mode ONFs (SM-ONFs) since only the fundamental guided mode is supported [16].…”
Section: Introductionmentioning
confidence: 99%
“…Evanescent wave devices have been commonly used with atomic systems for the past few decades [1,2], but more recently the integration of optical nanofibres, i.e. optical fibres with dimensions smaller than the wavelength of the guided light [3][4][5], into cold atomic systems [6][7][8] has been the focus of increasing research interest and a comprehensive review of progress is contained in [9]. In particular, it has been shown that optical nanofibres can be used for trapping and manipulating cold atoms.…”
Section: Introductionmentioning
confidence: 99%
“…The method is simultaneously corroborated with the standard free-space collection method. Finally, Russell et al (2013) perform release and recapture with an ONF to measure atomic temperature, as well as diagnose optical misalignment in their MOT setups.…”
Section: Atom-cloud Characteristicsmentioning
confidence: 99%